Long non-coding RNA FEZF1-AS1 facilitates non-small cell lung cancer progression via the ITGA11/miR-516b-5p axis - Song, Heng (Int J Oncol, 2020)
Long non-coding RNAs (lncRNAs) have emerged as key players in the development and progression of cancer. FEZ family zinc finger 1 antisense RNA 1 (FEZF1-AS1) is a novel lncRNA that is involved in the development of cancer and acts as a potential biomarker for cancer. However, the clinical significance and molecular mechanism of FEZF1-AS1 in non-small cell lung cancer (NSCLC) remains uncertain. In the present study, FEZF1-AS1 was selected using Arraystar Human lncRNA microarray and was identified to be upregulated in NSCLC tissues and negatively associated with the overall survival of patients with NSCLC. Loss-of-function assays revealed that FEZF1-AS1 inhibition decreased cell proliferation and migration, and arrested cells at the G(2)/M cell cycle phase. Mechanistically, FEZF1-AS1 expression was influenced by N6-methyladenosine (m(6)A) modification. Since FEZF1-AS1 was mainly located in the cytoplasmic fraction of NSCLC cells, it was hypothesized that it may be involved in competing endogenous RNA regulatory network to impact the prognosis of NSCLC. Via integrating Arraystar Human mRNA microarray data and miRNA bioinformatics analysis, it was revealed that ITGA11 expression was decreased with loss of FEZF1-AS1 and increased with gain of FEZF1-AS1 expression, and microRNA (miR)-516b-5p inhibited the expression levels of both FEZF1-AS and ITGA11. RNA-binding protein immunoprecipitation and RNA pulldown assays further demonstrated that FEZF1-AS1 could bind to miR-516b-5p and that ITGA11 was a direct target of miR-516b-5p by luciferase reporter assay. Overall, the present findings demonstrated that FEZF1-AS1 was upregulated and acted as an oncogene in NSCLC by regulating the ITGA11/miR-516b-5p axis, suggesting that FEZF1-AS1 may be a potential prognostic biomarker and therapeutic target for NSCLC.